Defining national research priorities for prostate cancer in Zambia: using the Delphi process for comprehensive cancer policy setting in sub-Saharan Africa - Ajay Aggarwal; Janet Seeley; Virginia Bond; Kennedy Lishimpi; John Kachimba; Musonda Simwinga; Andrew Sentoogo Ssemata; Susan Msadabwe; Dorothy Chilambe Lombe; Monde Mwamba; Richard Muhumuza; Victor Mapulanga (BMJ Oncology)
Objectives Locally led research on cancer is needed in sub-Saharan Africa to set feasible research priorities that inform national policy. The aim of this project was to develop a research agenda for national cancer control planning, using a nationally driven approach, focused on barriers to diagnosis and high-quality treatment for prostate cancer in Zambia.Methods and analysis This was a Delphi process. 29 stakeholders were scored barriers on feasibility, the proportion of patients affected, the impact on patient outcomes and if there was a potential to address health systems barriers meaningfully. There were three rounds (R) to the process: (R1 and R2) by electronic survey and (R3) in-person meeting. In R1 statements scoring above 15 from over 70% of participants were prioritised immediately for R3 discussion. Those scoring below 30% were dropped and those in between were re-surveyed in R2.Results 22 and 17 of the 29 stakeholders responded to R1 and R2. 14 stakeholders attended R3. National priority research areas for prostate cancer in Zambia were identified as prostate cancer awareness; building affordable high-quality diagnostic capacity; affordability of specialist cancer treatments; supporting better access to medicines; delivery and coordination of services across the pathway and staff training.Conclusion The suggested seven priority areas allow for the development of the prostate cancer control programme to be conducted in a holistic manner. The expectation is with this guidance international partners can contribute within the frameworks of the local agenda for sustainable development to be realised.